(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Cloacal malformation is a rare condition that usually referred only to females. We are reporting a very rare case of cloacal malformation variant in a 6-years-old boy who presented with absent anal opening along with hypospadiac penis with chordee with passage of urine and stool from an abnormal opening in the penoscrotal region. Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 52-53